Design and methods of a multi-component physical activity program for adults with intellectual disabilities living in group homes - Bik C. Chow; Wendy Y.J. Huang; Peggy H.N. Choi; Chien-yu Pan (Elsevier, 2016)
Adults with intellectual disabilities (ID) often live a sedentary lifestyle and have higher rates of overweight and obesity. The purpose of this report is to describe the design and methods of a multi-component physical activity (PA) intervention program that aims to increase PA levels in adults with ID who live in group homes. The study employed a multi-component delayed treatment control group design involving adults with ID who lived in two group homes. Interventions included 30 exercise sessions in groups over a 10-week period and three educational lessons based on social cognitive theory that aimed to improve self-efficacy and social support for PA in the participants. In addition, staff training in exercise and advice on institutional PA policies were provided to the caregivers working in the group homes. Outcome measures on three aspects were collected: (1) physical fitness, (2) PA as assessed by an ActiGraph accelerometer, and (3) self-efficacy and social support for PA. Our major objective was to develop the intervention protocol, and the successful completion of this study will provide valuable evidence on how to promote active lifestyles in adults with ID.